PENGARUH GOOD CORPORATE GOVERNANCE (GCG), UKURAN PERUSAHAAN DAN STRUKTUR MODAL TERHADAP KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020 – 2023 - Wahyuni, Vika Triya; Nugroho, Mulyanto (Bussman Journal : Indonesian Journal of Business and Management, 2024)
This study aims to analyze the effect of Good Corporate Governance (GCG), company size, and capital structure on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange during the period 2020-2023. The study population consists of listed manufacturing sector companies, with a sample of 54 companies selected using the purposive sampling method based on certain criteria. The data used are secondary data obtained from the financial statements for 2020 - 2023. The research method used is the quantitative method. Data analysis in this study was carried out using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) software. The results of the study indicate that only Good Corporate Governance (GCG) has a significant effect on financial performance, while company size and capital structure do not have a significant effect on financial performance. The Determination Coefficient (R Square) shows a value of 0.023, which means that the three independent variables explain 23% of the variability in financial performance, while 77% is explained by other variables outside the study.